Meta-Analysis of Serum Insulin-Like Growth Factor 1 in Alzheimer’s Disease - Ostrowski, Philip P.; Barszczyk, Andrew; Forstenpointner, Julia; Zheng, Wenhua; Feng, Zhong-Ping (PloS one, 2016)
Insulin-like growth factor 1 (IGF-1) serum levels have been reported to be altered in Alzheimer's disease patients, and it was suggested that the changes in IGF-1 serum level may play a role in disease pathology and progression. However, this notion remained controversial due to conflicting findings. We conducted a meta-analysis to determine the relationship between IGF-1 serum levels and Alzheimer's disease. We searched the databases PUBMED, Ovid SP, and Cochrane library for relevant studies. The primary data analyzed was serum IGF-1 from Alzheimer's disease subjects and controls. Pooled weighted mean difference using a random effects model was used to determine the relationship between serum levels and disease state. Nine studies were included in the meta-analysis compromising a total of 1639 subjects. The pooled weighted mean difference was -2.27ng/ml (95% CI: [-22.221, 17.66]) with a P value of 0.82. Thus our finding did not show clear relationship between low IGF-1 and Alzheimer's disease subjects. We did not find evidence of publication bias by analyzing a funnel plot as well as Egger's and Begg's tests. While eight out of the nine studies included in this meta-analysis detected a statistically significant increase or decrease in serum levels of IGF-1 in Alzheimer's disease subjects, the analysis as a whole did not show a significant trend in either direction. Thus, IGF-1 level is likely a critical personalized factor. A large database of clinical trials is required for better understanding the relationship between IGF-1 levels and Alzheimer's disease.